Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells. Issue 6 (November 2018) - Ruder, Barbara; Murtadak, Vinay; Stürzl, Michael; Wirtz, Stefan; Distler, Ute; Tenzer, Stefan; Mahapatro, Mousumi; Greten, Florian; Hu, Yinling; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; et al.
Abstract Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression ofvFlip disrupts tissue homeostasis and induces severe intestinal inflammation. MoreovervFlip IEC-tg mice showed reduced Paneth cell numbers, associated with excessive necrotic cell death. On a molecular levelvFlip expression altered classical and alternative NFκB activation. Blocking of alternative NFκB signaling by deletion ofIkka in vivo largely protected mice from inflammation and Paneth cell loss induced by vFLIP. Collectively, our data provide functional evidence that expression of a single viral protein in IECs can be sufficient to disrupt epithelial homeostasis and to initiate chronic intestinal inflammation.